Al-Hājat As The Basis Of Contemporary Ijtihād - Fatarib, Husnul; Qasem, Muhammad; Meirison, Meirison (al-'adalah, 2020)
This article discusses the use of the concept of hājat (necessity)  in the application of sharia law when there are difficulties in applying the original provisions. The hājat (necessity) makes it possible for people and individuals not to apply the original law when they experience difficulties in applying it. However, the use of hājat must fulfill several conditions, including (1) it should be mu'tabarah, not contradicting the prevailing principles of syara', (2) it should be found in cases that seriously threaten religious interests, life/soul, mind, descent, and property. (3) If the hājat is general for a group of people or the wider community or individuals, then this position of hājat occupies an emergency position and takes place permanently for the community but temporarily for individuals. This study found the fact that some contemporary scholars no longer adhere to the principle of hājat which is mu'tabarah or following the maqāsid sharī'ah with all its requirements but has mixed it with pseudo-ad-dharūrah (emergency). Through this approach, some contemporary cases that were initially considered harām (forbidden), such as forex (Foreign Exchange) are considered lawful because they are needed. In other words, even though it is not a real hājat because forex is ribā nasī'ah, it can be done in an emergency, as is the case with bonds that have fixed interest.